Association of oral health knowledge, self-efficacy and behaviours with oral health-related quality of life in Chinese primary school children: a cross-sectional study. Issue 12 (15th December 2022) - Zhao, Jie; Shi, Hongyan; Wang, Jingya; Huang, Rui; Liu, Yongyi; Zhang, Yuxin; Jiang, Nan; Wang, Ting; Wang, Jiwei; Xu, Xiaoming
Abstract : Objective: Achieving good oral health-related quality of life (OHRQOL) is of particular concern in children. The inter-relations among oral health knowledge, self-efficacy, behaviours and OHRQOL in children groups remain unclear. This study aimed to explore the inter-relations between these oral health behaviour-related factors and OHRQOL in primary school children. Methods: In this cross-sectional study, 651 children in grades 2 and 3 were recruited in October 2020 from two primary schools in Minhang District, Shanghai, China. Data were collected through self-reported questionnaires, consisting of demographic characteristics, oral health knowledge, self-efficacy, oral health behaviours and OHRQOL. Pearson's correlation analyses were used to analyse the relationship between study variables. Structural equation models were used to test the inter-relations between OHRQOL and oral health behaviour-related factors. Results: Four hypothetical structural equation models were tested and one of them was selected as the most appropriate model, which explained 15.0% of the variance in OHRQOL. This selected model showed that oral health behaviours were directly related to OHRQOL. Oral health knowledge was indirectly associated with OHRQOL through both self-efficacy and oral health behaviours. Self-efficacy was directly associated with OHRQOL or was indirectly associated with OHRQOL through oral health behaviours. Conclusion: This study revealed a pathway of association between children's oral health knowledge and their OHRQOL, in which children's oral health self-efficacy and behaviours had indirect effects. This provides a basis for understanding the mechanism of oral health promotion interventions to improve children's OHRQOL and helps to identify direct or indirect intervention targets.